Antagonistic of trichoderma species against some plant pathogenic soil fungi on carnation - Baghdad Science Journal (مجلة بغداد للعلوم, 2005)
Adhrt all fungal biological control ability Tdhadah less than 2 repel Alaftran Almamradan showed leaky mushroom Biological control is thermally laboratories and different concentrations of 5, 10 and 20% inhibition in the growth of fungus colonies amounted to 3.8 cm and 3.1 and 2.4 respectively in comparison with control 9 cm